2020
DOI: 10.1128/aac.02168-19
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Binding to the O-Specific Antigen of Pseudomonas aeruginosa O6 Inhibits Cell Growth

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that is inherently resistant to many antibiotics and represents an increasing threat due to the emergence of drug-resistant strains. There is a pressing need to develop innovative antimicrobials against this pathogen. In this study, we identified the O-specific antigen (OSA) of P. aeruginosa serotype O6 as a novel target for therapeutic intervention. Binding of monoclonal antibodies and antigen-binding fragments therefrom to O6 OSA leads to rapid outer membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…35 In another study, Richard et al confirmed that the S20 scFv exerted its antibacterial activity through binding to the Ospecific antigen of P. aeruginosa (serotype O6), leading to the outer membrane disruption, followed by bacterial death. 34 The direct bactericidal activity of scFv fragments can be explained by their function as AMPs 35,37,38 or catalysis of some chemical reactions (e.g. abzymes), 35 besides interference with the biological function of the bacterium as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35 In another study, Richard et al confirmed that the S20 scFv exerted its antibacterial activity through binding to the Ospecific antigen of P. aeruginosa (serotype O6), leading to the outer membrane disruption, followed by bacterial death. 34 The direct bactericidal activity of scFv fragments can be explained by their function as AMPs 35,37,38 or catalysis of some chemical reactions (e.g. abzymes), 35 besides interference with the biological function of the bacterium as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] A group of scFvs has been generated against pathogen targets, 32 some of which showed direct bactericidal activities. [33][34][35][36] These antibacterial scFvs seem to exert their bactericidal effects by disrupting the bacterium's biological activity, compromising the cell wall integrity or functioning as abzymes. 35,[37][38][39] In this regard, Wang et al isolated eight high-affinity anti-S. aureus scFvs from a phage-display library, which was constructed from the peripheral blood lymphocytes of cows with mastitis caused by S. aureus.…”
Section: Dsta4637smentioning
confidence: 99%
See 2 more Smart Citations
“…candidates and immunization trials targeted many compartments of P. aeruginosa such as external proteins, like flagella (8,9) and pili (10), cytosolic protein (11), outer membrane proteins (12,13), alginate which is an extracellular polysaccharide (14), lipopolysaccharide (15), capsular antigen (16), somatic antigen known as "O antigen" (17,18), and biofilm (19).…”
Section: Razook Et Almentioning
confidence: 99%